Advances and controversies in emerging techniques of surgery on breast cancer - ZHANG Yujia, MA Li (Zhongguo aizheng zazhi)
Breast cancer is one of the most common malignant tumors in women, which posing a serious threat to women's health. With the deepening of the concept of precision treatment, the surgical treatment of breast cancer has made great progress. However, new techniques and ideas have also brought about many controversies. With the popularization of the “de-escalation” concept, performing sentinel lymph node biopsy (SLNB) as an alternative to axillary lymph node dissection (ALND) in specific patients has emerged as a trend. For clinically node-negative early-stage breast cancer with 1-2 positive sentinel lymph nodes (SLN), ALND can be safely omitted with effective axillary radiotherapy. Patients with clinically node-positive early-stage breast cancer can forgo ALND if SLNB proves that they have been downstaged to cN0 by neoadjuvant treatment (NAT). As the two most commonly used axillary surgical staging techniques in SLNB for post-NAT patients, dual-tracer of lymph nodes and targeted axillary dissection (TAD) are considered consistent in oncologic safety. Prophylactic mastectomy is a significant intervention to reduce breast cancer incidence among women at high risk. It has been confirmed that contralateral prophylactic mastectomy (CPM) can reduce the incidence of contralateral breast cancer (CBC) but does not significantly improve the survival outcomes. Enhancing the accessibility of risk assessment methods and establishing precise and effective risk prediction models have emerged as important issues. Above all, the development of breast surgery shows a refinement of risk management and damage control, striving to achieve a safe “de-escalation” in surgical modalities based on individualized treatment. This article summarized and analyzed relevant studies on the aspect of the surgery techniques for breast cancer, aiming to provide new insights into optimizing the clinical diagnosis and treatment of breast cancer.